O sistema de avaliação nacional e a educação escolar indígena : contrastando duas realidades a partir do ensino de ciências - Santos, Hélio Magno Nascimento dos (2015)
This research introduces educational quality indicators, focusing on indigenous educational modality. Thus, the problem of this research is the relation between the quality indices of national education and school education offered to indigenous population, seeking in this context to produce elements to reflect on the teaching of natural sciences. The overall objective of this research is to reveal the relation between the quality data of national education, and indigenous education as a way to contribute to the reflection of the relevance (or not) of the school performance test proposition that include, especially, the natural sciences in school indigenous education (EEI - Escola de Educação Indígena). The methodology used has a qualitative-quantitative/theoretical-bibliographic approach, more predominantly qualitative approach. Data collection was done through reading, and analysis of academic productions, and official documents that specifically point the national education quality indicators, and EEI, also through the open questionnaire, carried out with the state departments of education of all states. Initially, we discussed the Brazilian assessment system, taking into consideration the main educational statistics in Brazil. We tried to approach as following, the organization of the national education system, its modalities, and education quality indicators with emphasis on ERA. Among the indicators of educational quality which include the evaluation of EEI, the following ones were discussed: the registration, training of teachers, educational establishments, the specific educational resources for indigenous schools, and school performance in external evaluations. Afterwards, we approached the reality of two indigenous schools, one of them is in Mato Grosso State, chosen because surveys have been carried out in such institution during the PhD studies that anticipate this work. The second school establishment is located in Sergipe State, It is chosen as the only of this type in the state and due to activities of the Institutional Scholarship Program for Initiation to Teaching (PIBID) in school. These activities are developed by the students of the UFS (Campus Itabaiana), PIBID Scholars. From the results, it is clear that the ERA is established throughout the country, except for the Federal District. We present yet, data about the teaching of Natural Sciences in this type of education, based on observation of the aforementioned two Indian schools. In this last step, we seek to unveil, from official documents and publications of the members of the "Study Group Science Education, Diversity and Environment", some indices of educational quality. In closing remarks, reflect the above items, underscoring the perception that, over the past two decades, significant advances have been achieved by indigenous peoples; However, according to studies, it is clear that there is still much to do in promoting and ensuring a quality ERA.